A clinical and histopathological study of nevus sebaceous - Puri, Neerja (Journal of Pakistan Association of Dermatologists, 2016)
Objective To study the clinical and histopathological features of nevus sebaceous (NS). Â Methods We selected 20 cases of nevus sebaceous for clinical and histopathological evaluation. Â Results Regarding the clinical appearance of lesions verrucous plaques were seen in 60% patients, papules in 25% and patches in 15%. All of the lesions showed abortive/immature hair follicles characterized by cords of undifferentiated, basaloid cells resembling the embryonic stages of hair follicle. Â Conclusion NS is a hamartoma consisting of various elements indigenous to the organ and not merely the sebaceous units. Â